Functional Delay Test Construction Approaches - Bareiša, E.; Jusas, V.; Motiejūnas, K.; Šeinauskas, R. (Elektronika ir Elektrotechnika, 2007)
It is explored how functional delay tests constructed at algorithmic level detect transition faults at gate-level. Main attention was paid to investigation of the possibilities to improve the transition fault coverage using n-detection functional delay fault tests. The proposed functional delay test construction approaches allowed achieving 99 % transition fault coverage which is acceptable even for manufacturing test. Bibl. 18 (in English; summaries in English, Russian and Lithuanian).